COMPARATIVE EVALUATION OF MAGNETIC RESONANCE CHOLANGIOPANCREATOGRAPHY AND PERIOPERATIVE CHOLANGIOGRAPHY IN PATIENTS WITH SUSPECT CHOLEDOCHOLITHIASIS - PERALES, Simone Reges (Arq Bras Cir Dig, 2019)
BACKGROUND: Cholelithiasis is a highly prevalent condition, and choledocholitiasis is a high morbidity complication and requires accurate methods for its diagnosis. AIM: To evaluate the population of patients with suspected choledocholitiasis and check the statistical value of magnetic resonance cholangiopancreatography, ultrasonography, the laboratory and the clinic of these patients comparing them to the results obtained by perioperative cholangiography. METHODS: This is a retrospective cohort study, which were evaluated 76 patients with cholelithiasis and suspected choledocholithiasis. RESULTS: It was observed that the presence of dilatation of the biliary tract or choledocholithiasis in the ultrasonography was four and eight times increased risk of perioperative cholangiography for positive choledocholithiasis, respectively. For each unit increased in serum alkaline phosphatase was 0.3% increased the risk of perioperative cholangiography for positive choledocholithiasis. In the presence of dilatation of the bile ducts in the ultrasonography was four times greater risk of positive magnetic resonance cholangiopancreatography for choledocholithiasis. In the presence of pancreatitis these patients had five times higher risk of positive magnetic resonance cholangiopancreatography for choledocholithiasis. On the positive magnetic resonance cholangiopancreatography presence to choledocholithiasis was 104 times greater of positive perioperative cholangiography for choledocholithiasis. CONCLUSIONS: The magnetic resonance cholangiopancreatography is a method with good accuracy for propedeutic follow-up for the diagnosis of choledocholithiasis, consistent with the results obtained from the perioperative cholangiography; however, it is less invasive, with less risk to the patient and promote decreased surgical time when compared with perioperative cholangiography.